Ethnicity and race : creating educational opportunities around the globe - Brown, Elinor L.; Gibbons, Pamela E. (International advances in education., 2011)
This volume of Global Initiatives for Equity and Social Justice takes a resource perspective toward culture, ethnicity, and race. Its purpose is to foster global dialog about race and ethnicity, with an emphasis on sharing strategies and solutions. While one might view problems stemming from racial and ethnic differences as intractable, the book's editors and chapter authors wisely and creatively move through and beyond challenges and barriers by highlighting and sharing models, programs, frameworks, and strategies that are making a positive difference. Chapters provide examples and discussions relevant to the K-12 levels, as well as higher education and professional preparation in fields that include teacher education, social work, and medical education. Chapters grapple with complexities such as tensions among colonization, nation building, and ethnic identity. Chapters explore potentials of information technology for opening access to education and building dialogue across differences. Elinor Brown and Pamela Gibbons offer us a much-needed volume that, with clear recognition of problems of the present and past, looks optimistically toward the future.